Supporting Mental Well-Being Through Emotion-Focused Coaching Intervention - Kovbuz, Valeriya (European Scientific Journal, ESJ, 2025)
Emotion-Focused Coaching (EFC) is a new method focused on expanding emotional intelligence and psychological well-being, which does not involve therapeutic work. The current conceptual paper suggests a theoretical literature review to analyze the peer-reviewed sources on how EFC can promote emotional awareness, self-compassion, resilience, and better interpersonal relationships. EFC does not involve clinical intervention, unlike other traditional forms of therapeutic interventions; it offers a structured means through which the individual interacts with his thoughts and feelings. According to the literature, coaching clients tend to become more empathetic communicators and also develop greater skills in conflict resolution, both personal and professional. Possible use of EFC in the learning process, medical practice, and workplace is also explored as an early solution to emotional support. The method demands well-trained special coaches who effectively work in an emotional facilitation context and clients who are ready to practice self-reflection. All in all, EFC proves to be a revolutionary model of self-growth and a resourceful addition to the upcoming sphere of coaching and mental support.